Gender differences in major depressive disorders: A resting state fMRI study - Tu, Zhaoyuan; Wu, Feng; Jiang, Xiaowei; Kong, Lingtao; Tang, Yanqing (Frontiers in Psychiatry, 2022)
Background: Major depressive disorder (MDD) has a high disability rate and brings a large disease burden to patients and the country. Significant sex differences exist in both the epidemiological and clinical features in MDD. The effect of sex on brain function in MDD is not clear now. Regional homogeneity (ReHo) and ALFF are widely used research method in the study of brain function. This research aimed to use ReHo and ALFF to explore gender differences in brain function images in MDD. Methods: Eighty first-episode drug-naive patients (47 women and 30 men) with MDD and 85 age, education matched healthy volunteers (47 women and 31 men) were recruited in our study and participated in resting-state functional magnetic resonance imaging scans. ReHo and ALFF was used to assess brain activity, two-way ANOVA and posthoc analysis was conducted to explore the sex difference in MDD. Correlation analysis was used to explore the relationship between abnormal brain functioning and clinical symptoms. Results: we observed sex-specific patterns and diagnostic differences in MDD Patients, our further post hoc comparisons indicated that women with MDD showed decreased ALFF value in the right superior occipital gyrus and decreased ReHo value in the left calcarine and left dorsolateral superior frontal gyrus compared with HC females and men with MDD. Men with MDD showed decreased ReHo value in the right median cingulate gyrus compared with HC males and increased ReHo value in the left dorsolateral superior frontal gyrus compared with HC males, we also found that in HC males showed increased ReHo value in the right median cingulate gyrus compared with HC females. Conclusions: men and women do have sex differences in brain function, the occipital lobe, calcarine, DLPFC, and DCG were the main different brain regions found in our study between male and female in MDD, which may be the biomarker brain regions that can help diagnose and treat MDD in men and women.